Reception as a unity of cultural and historical memory, oblivion, and imagination - N.A. Tereshchenko; T.M. Shatunova (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article is dedicated to the memory of Evgenii Aleksandrovich Chiglintsev, a brilliant historian, an outstanding representative of the university intelligentsia, and a wonderful comrade with the best human qualities. E.A. Chiglintsev’s works are interdisciplinary, useful for practically all humanities, and certainly important from the philosophical and socio-philosophical perspectives. The study aims to analyze and evaluate the phenomenon of cultural reception in the context of E.A. Chiglintsev’s writings. The main problematic field of the article is the meanings, boundaries, and prospects of the phenomenon of reception, which has become one of the main subjects of E.A. Chiglintsev’s research interest. E.A. Chiglintsev focused mostly on the universal meaning of reception, whereas this article also considers its historical backgrounds, as well as the possibilities and meanings of cultural and historical receptions in the modern culture and society. The research is relevant due to the practical need to develop an adequate attitude to the past in the modern society, i.e., because of the need to distinguish what and in what forms should be remembered, what and how to forget, how to take fire from the past, not ashes. Today, every person who considers himself or herself modern must constantly undergo the path of rethinking his or her historical past, and thus participate in the reception of past cultures. The conclusion is made about the historicity of reception, the classical forms of which are developing in the modern culture, about the problematic nature of this phenomenon in the postmodern culture. The problem of further development of the meaning of reception in the modern culture and its limits is posed.